(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2025)
This article presents a reflection on the development of the concept of Mnemonic Corporality in the performative context. The described process is based on life stories and dialogue with Brazilian popular oral traditions. The narrative highlights the journey of an individual engaged in the struggle for land, expressing their aesthetics through the articulation of body and voice, which manifests in various images, sounds, and musicalities. The performative creations suggest a form of expression deeply rooted in the body’s history and in a spiral of memories performed as sonorities in dance.